Perspectives adopted by caregivers in the interaction with the institutionalized child - Ruth Irmgard Bärtschi Gabatz; Eda Schwartz; Viviane Marten Milbrath (Universidade Federal de Santa Maria, 2019)
Aim: To understand the perspectives of the caregivers based on their interaction with the institutionalized children. Method: A qualitative research using Grounded Theory and Symbolic Interactionism for data elaboration and analysis. Data was collected from April to July 2015, through an intensive interview, with 15 caregivers in a child care institution. Results: They are presented in three categories: Learning to value life and family; Changing the way you see and deal with others; Understanding the child as a person capable of changing their reality. Final considerations: It was identified that, in the interaction with the institutionalized child, the caregiver starts adopting new ways of seeing and acting in the world, valuing her life and family, besides developing more patience, compassion and love for other people in conditions of vulnerability.